2011
DOI: 10.1371/journal.pone.0014510
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Receptor Site on Insect Sodium Channel for Depressant β-toxin BmK IT2

Abstract: BackgroundBmK IT2 is regarded as a receptor site-4 modulator of sodium channels with depressant insect toxicity. It also displays anti-nociceptive and anti-convulsant activities in rat models. In this study, the potency and efficacy of BmK IT2 were for the first time assessed and compared among four sodium channel isoforms expressed in Xenopus oocytes. Combined with molecular approach, the receptor site of BmK IT2 was further localized.Principal Findings2 µM BmK IT2 strongly shifted the activation of DmNav1, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Nevertheless, these non-functional contact points can also be a requirement for the full activity of the toxin. He et al ( 2011 ) recently described this for binding of BmK IT2, a site 4 insect β-toxin from Buthus martensii Karsch, to insect DmNa v VGSCs. Mutations in the site 4 binding area (DII S3–S4) largely abolished the functional action of BmK IT2 on DmNa v .…”
Section: Revision Of Neurotoxin Binding Sitesmentioning
confidence: 98%
See 1 more Smart Citation
“…Nevertheless, these non-functional contact points can also be a requirement for the full activity of the toxin. He et al ( 2011 ) recently described this for binding of BmK IT2, a site 4 insect β-toxin from Buthus martensii Karsch, to insect DmNa v VGSCs. Mutations in the site 4 binding area (DII S3–S4) largely abolished the functional action of BmK IT2 on DmNa v .…”
Section: Revision Of Neurotoxin Binding Sitesmentioning
confidence: 98%
“…However, some anchor points in DIII turned out to be responsible for the selective recognition of the insect channel over the rat Na v 1.2 channel. In addition, the N-terminal part of the S5–S6 linker (SS2–S6) in this DIII greatly influenced the potency of the BmK IT2 binding to DmNa v (He et al, 2011 ).…”
Section: Revision Of Neurotoxin Binding Sitesmentioning
confidence: 99%
“…The patch-clamp experiment also proved that BmK IT2 can inhibit the persistent sodium current of hippocampal pyramidal neurons [59]. However, previous studies have found that BmK IT2 had no significant inhibitory effect on the peak Na + currents of Nav1.2, 1.3, and 1.6 heterologous-expressed in oocytes [51]. It is suggested that BmK IT2 might act on Nav1.1 or Nav1.7 in the central nervous system (CNS).…”
Section: Antiepileptic Activity Of Bmk Toxins 31 Antiepileptic Activmentioning
confidence: 93%
“…In fact, the inhibition of BmK IT2 on total Na + currents was observed in small DRG neurons [13]. By testing VGSC subtypes in Xenopus oocytes expression system, Nav1.2, Nav1.3, and Nav1.6 display insensitive property to BmK IT2, suggesting that other isoforms, especially Nav1.7-1.9, might be involved in the suppressive activity of BmK IT2 in rat pathological models [51]. The results illuminated that BmK IT2 can be developed as a novel analgesic peptide with therapeutic potential.…”
Section: Analgesic Effects Of Bmk Toxins Against Vgscsmentioning
confidence: 99%
“…Analysis of subsequent DmNa v 1 mutants further highlighted that, in addition to the contribution of E896, L899, and G904 in DII S4 for functional action of BmK IT2, residues in DIII pore loop, esp. I1529 and R1530, were critical for recognition and binding of BmK IT2 (He et al 2011). Hence, DIII SS2-S6 is considered to be the recognition site with species selectivity for BmK IT2 and DII S3b-S4 is considered the functional voltage-trapping site of VGSCs.…”
Section: Pharmacological and Molecular Mechanisms Of Bmk Toxins Intermentioning
confidence: 99%